Book review: Di Nunzio, Marco. 2019: The Act of Living: Street Life, Marginality and Development in Urban Ethiopia. (July 2020) - Cochrane, Logan
Di Nunzio, Marco. 2019: The Act of Living: Street Life, Marginality and Development in Urban Ethiopia . Ithaca, NY: Cornell University Press. 245 pp. US$115. ISBN-13: 978-1501736261 (Hardcover).